ETIOTROPIC AND SYMPTOMATIC THERAPY OF ACUTE RESPIRATORY INFECTIONS - V.К. Tatochenko (Педиатрическая фармакология)
Acute respiratory infections are the most widely spread pathology in the children. They do not belong to the category of severe, incapacitating diseases, but they considerably worsen the general condition of the child and are dangerous through their life threatening complications. It is very important to start the etiotropic antiviral therapy and whenever possible, quickly to stop disease manifestations, without any harm for child. The proposed article is devoted to the optimization of the symptomatic therapy in the event of the given pathology.Key words: acute respiratory infections, symptoms, treatment, children.